Development, microbiological and physicochemical analysis of kombucha-based fermented beverage - Oliveira, Anolivia Arruda de (2020)
Fermented kombucha-based beverages have been gaining many adepts around the world because their consumption is associated with beneficial effects on the intestinal microbiota and in some chronic diseases. However, such effects are related to the quality of the drink in terms of microbiological and physicochemical aspects. This study aimed to develop and analyze the microbiological and physicochemical quality of a grape-flavored kombucha fermented drink. This is a quantitative, descriptive, and laboratory study. For the production of the drink, the first fermentation was conducted for five days. Subsequently, the drink was savored simultaneously with the second fermentation with a containing method that guaranteed anaerobic conditions. The beverage was analyzed on the day of filling (Time 0) and on the third day of fermentation (Time 3), regarding the microbiological aspects (total coliforms, presence of Salmonella spp., lactic and acetic bacteria) and physicochemical (pH, acidity, ºBrix). It was not identified in any of the total coliform, thermotolerant, and Salmonella spp. Regarding lactic acid bacteria, they predominated in Time 3 while acetic bacteria in Time 0. As for the physicochemical parameters, pH values ​​were high during the fermentation process (ranging from 3.5 to 3.78), acidity was constant (7.5%) and a slight reduction was observed for the soluble solids on days 0 and 3 (9.0 and 8.5, respectively). As for microbiological standards, the analyses attested to the satisfactory quality of the drink produced. Regarding the physical-chemical parameters, it was observed that the pH values ​​were above the established by the legislation.